2010
DOI: 10.1111/j.1757-7861.2010.00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical research on the bio‐debridement effect of maggot therapy for treatment of chronically infected lesions

Abstract: Maggot therapy is a safe and effective method for treating chronically infected lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 26 publications
0
25
0
4
Order By: Relevance
“…The use of larval therapy to enhance wound healing remains unsupported with only five studies identified, each of which had a high risk of bias …”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of larval therapy to enhance wound healing remains unsupported with only five studies identified, each of which had a high risk of bias …”
Section: Recommendationsmentioning
confidence: 99%
“…11 The use of larval therapy to enhance wound healing remains unsupported with only five studies identified, each of which had a high risk of bias. [12][13][14][15][16] Overall, there are data of low quality to suggest that debridement of some sort is beneficial and effective, but insufficient good quality evidence to support one form of debridement over another. Current expert opinion recommends that sharp debridement should be adopted in preference to other techniques, particularly as this is the least expensive of the methods and available in all geographic areas.…”
Section: Rationalementioning
confidence: 99%
“…Another retrospective study by Wang et al followed 25 diabetic foot ulcers and 18 pressure ulcers in spinal cord-injury patients treated with either MDT or traditional dressings. 27 The MDT group had a significantly shorter time to achieve bacterial negativity, healthy granulation, and complete healing. Finally, the most recent RCT was conducted in 2014 at the Wound Healing Research Unit, Cardiff University by Mudge et al 28 This study compared the clinical effectiveness of a larval therapy dressing (Bio-FOAM) with a standard debridement technique (Purilon gel; hydrogel) in terms of time to debridement of venous or mixed arterial/venous leg ulcers.…”
mentioning
confidence: 99%
“…Only one recent retrospective controlled cohort study at a high risk of bias 17 was found in addition to the four studies previously reported. [18][19][20][21] All four of the older studies were at high risk of bias, non-randomized, and unblinded. Any apparent effect of improved healing should therefore be treated with caution.…”
Section: Larval Therapymentioning
confidence: 99%